Factors influencing the choice of private medical centre among Malaysians - Kamarohim, Nor Azlina; Turmin, Siti Zaidah; Othman, Manisah (Universiti Putra Malaysia Press, 2013)
With better education, knowledge and income, people today are able to choose the medical services that will satisfy them the most. The purpose of this study is to examine the factors influencing consumers in choosing a Private Medical Centre. In this study, five factors were used and these included waiting time, environment, reputation of consultant, facilities and cost. These factors had been used to see whether they influenced the choice for private medical centre among Malaysians. Data were collected through a questionnaire survey that involved customers of private medical centre in Serdang, Kajang, and Puchong. Convenience sampling technique was used to distribute 155 questionnaires. The results showed that there was a significant relationship between environment, facilities, and cost, with the choice of Private Medical Centre among Malaysians. Based on the results, it is suggested that the management of Private Medical Centre should focus on providing the best services to their customers to ensure they get the greatest satisfaction.